Journalism and technological change historical perspectives, contemporary trends (Campus Verlag, 2014)
"This volume not only considers the implementation--the successes and failures--of new media technologies, but also the influence these technologies have had both on the practical demands and internal processes of media companies and on the professional roles, social positions, and self-perceptions of journalists. A thorough, interdisciplinary synthesis covering more than one hundred and fifty years of media in Europe and the United States"--From distributor's website.